ON LOWER SEMICONTINUITY OF THE SOLUTION MAPPINGS OF THE VECTOR EQUILIBRIUM PROBLEMS - Farajzadeh, A.P.; Shafie, A.K. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2019)
By using a new assumption, the lower semicontinuity of the solution mapping of the vector equilibrium mappings in the setting of topological vector spaces without using a continuity assumption are established. Some examples in order to illustrate the main results are given. The results of the article can be viewed as improvements to the results published in this area.